The Early Years of American Political Science: Traditionalist Paradigm and its Critics - Iftikhar Ahmad (Research in Social Sciences and Technology, 2016)
American political science has a checkered history. In the first decade of the twentieth century the discipline of political science was in its nascent stage. Political science professors of that period espoused a worldview that may be called Traditionalism. Traditionalist paradigm was informed by Hegelian philosophy and its main thrust was the study of the state. Traditionalism promoted teaching about the structure and function of government on college campuses and in public schools packaging it as citizenship education. However, political scientists of the mid-1920s and early 1930s found Traditionalism to be an inadequate methodology for explaining the complex political problems of the industrial age. Thus Behavioralism emerged as a new paradigm making Traditionalism obsolete. Behavioralist paradigm also could not explain adequately the causes of the nation-wide social unrest and racial conflicts of the 1970s, and hence it too lost its respectability, especially among women and other disenfranchised political scientists in American academia.